Combined Use of External Iliac Lymph Node Count and Bone Scintigraphy for PJI Diagnosis: A Prospective Study - Haotian Zhou; Yaji Yang; Jia Li; Qianshui Hu; Feilong Li; Leilei Qin; Wei Huang; Hai Wang; Qiang Cheng (Diagnostics)
Background: The reactive enlargement of external iliac lymph nodes and increased blood flow in the infected region are commonly observed in lower limb infections. We aimed to differentiate between aseptic loosening and periprosthetic joint infection (PJI) after joint replacement surgery by quantifying the number of enlarged external iliac lymph nodes and using bone scintigraphy to monitor blood flow. Methods: We recruited 124 patients undergoing revision surgery for aseptic loosening or PJI. All the patients underwent preoperative dual-energy computed tomography (DECT) imaging for external iliac lymph nodes and bone scintigraphy. The diagnostic value was evaluated using ROC curve analysis. Results: The number of enlarged external iliac lymph nodes was significantly higher in the PJI group than in the aseptic failure group (4.0 versus. 1.0, p value < 0.001). The median affected/unaffected side ratio in the blood pool phase of ECT in the PJI group was 1.49, significantly higher than the aseptic failure group’s median ratio of 1.04 (p value < 0.001). The AUC for diagnosing PJI using the number of enlarged lymph nodes alone was 0.91, and when using the bone scintigraphy blood pool phase alone, the AUC was 0.89. When both metrics were combined, the AUC increased to 0.95, which was higher than the AUCs for the ESR (AUC = 0.83), CRP (AUC = 0.76), and synovial fluid PMN% (AUC = 0.62). Conclusions: Combining the enlargement of the lymph node count with the bone scintigraphy blood pool phase is a promising approach for diagnosing PJI.